DAMPAK PENERAPAN SMM ISO 9001:2000 TERHADAP KUALITAS LAYANAN AKADEMIK DAN LULUSAN FT UNY - Sugiyono, Sugiyono; Nuryanto, Apri; Mulyatiningsih, Endang (Jurnal Pendidikan Teknologi dan Kejuruan, 2011)
ABSTRACTThis research aims at revealing the impact of the implimentation of ISO 9001:2000 towards the academic service quality (the service quality of lecturers, staffs, technicians, and department orginizer) and the graduates’ quality (GPA and period of study). This evaluation was conducted by using descriptive research method and document analysis to reveal the fact of academic service beforeand after the implementation of ISO 9001:2000. The sample technique was using cluster sampling technique as PTM and PTTB departments were chosen. The target sample was 83 students in the seventh semestser and the dacuments in ISO secretariat from those two deperatments. Data collection techniques were using questionnaire and documentation (syallabus and lesson plan, yusisum data, learning evaluation, attandence list and assessement document). Data analysis method was using quatitive descriptive analysis. The findings showed the mean scores of acedemic sevice quality in PTBB Department had been fulfilling the expectation (3,12) while for PTM can be categorized as moderate level (2.97). The lowest score was found in the area of academic administration service, i.e. 3,02 for PTBB and 2,83 for PTM. Furthermore, it was found that The quality of PTBB graduates improved 0,02 and the period of study for (S1/ Bachelor degree) fluctuated in 5,16 while the GPA of PTM was not stable yet but the students had shorter period of study. By seeing the findings, it can concluded that the implementation of ISO 9001-2000 was able to improve the administration service of academic but it did not guarantee to create qualified acadmic service to support the fulfilment of high GPA and short period of study.Keywords: graduates’ quality, SMM-ISO 9001-2000, quality of academic service